Teachers’ Readiness to Accommodate Diverse Students Through Distance Learning in an Inclusive Setting - Dinar Westri Andini; Ahmad Hufad; Ayu Rahayu; Yohana Sumiyati; Abdul Rahim; Taryatman Taryatman (Department of Special Education, 2021)
Learning must be accessible to all students. Therefore, significant challenges face developing distance learning that can meet the learning needs of every student diversity, including the student with special needs. Therefore, this study aims to describe the teacher readiness to meet the student learning needs through distance learning in schools by providing inclusive education. The research method used a questionnaire in 173 teachers from elementary schools in five districts in the Special Region of Yogyakarta (DIY) by asking them the questions such as the ease of internet networks, learning tools and equipment used, the selected learning management system (LMS) and provides the open-ended questions in the form of advantages and difficulties in distance learning. Indeed, the study results indicate that to increase teacher readiness, such as the efforts are needed and a positive atmosphere that can form self-development and self-efficacy culture